Airborne pollen and fungi indoors: Evidence from primary schools in Lithuania. Issue 1 (January 2023) - Sauliene, Ingrida; Valiulis, Arunas; Keriene, Ilona; Sukiene, Laura; Dovydaityte, Dovile; Prokopciuk, Nina; Valskys, Vaidotas; Valskiene, Roberta; Damialis, Athanasios
Abstract: The number of children suffering from respiratory allergies and asthma has been increasing worldwide and, hence, it is crucial to understand the burden of inhalant biological particles present in school facilities, where children spend one third of their life. From the perspective of indoor air quality, while there are numerous studies on outdoor bioaerosol exposure, there are still uncertainties regarding the diversity and deposition of airborne pollen and fungi indoors. When it comes to schools, there is limited research as to the potential bioaerosol exposure. Here we studied the indoor environment of public schools aiming to reveal whether primary schools of different sizes and at localities of different levels of urbanization may exhibit a variability in the biodiversity and abundance of particles of biological origin, which could pose a risk to child health. To achieve this, 11 schools were selected, located in a variety of environments, from downtown, to city centre-periphery, and to the suburbs. Fungal and pollen samples were collected from various surfaces in school classrooms and corridors, using passive air sampling and swab sampling. We demonstrated that fungi and pollen are detected in school premises during and after the vegetation season. The highest diversity of bioaerosols was found on the top of cabinets and windowsills, with Penicillium, Cladosporium and Acremonium being the most abundant indoors. The levels of fungi were higher in schools with more students. The diversity and amount of pollen in the spring were significantly higher than in samples collected in autumn. Our findings complemented existing evidence that bioaerosol measurements in schools (including kindergartens or informal education facilities) are vital. Hence, we here suggest that, in addition to monitoring air quality and bacterial levels indoors, fungi and pollen measurements have to be integrated in the existing regular biomonitoring campaigns so as to prevent exposure, increase awareness and manage efficiently allergic symptomatology.